2019
DOI: 10.1080/13102818.2019.1568914
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger CCHC-type protein related with seed size in model legume species Medicago truncatula

Abstract: Legumes are one of the world's leading sources of nutrition, providing sustainable agriculture. They require minimal amounts of soil improvers (fertilizers) due to the ability to absorb nitrogen through symbiotic interactions with nitrogen-fixing soil microorganisms. The trend for human population growth requires an adequate growth in crop production. This directly depends on the seed size and number as well as on the leaf biomass. In turn, seed size has been the subject of selection programmers for all crops.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…In the case of the SNP associated with seed length and width, dDocent_Contig_466_145, it is possible that the identified Znf-C2HC domain, downstream of the GAG domain of the TE is playing a role in gene transcription and thus affecting seed size. This would be similar to what has been reported for the ZnF-C2H2 domain encoding gene that was identified in M. truncatula and which was found to affect seed size [ 55 ]. Our further investigation of the protein sequence suggests that it is a truncated form of a similar multi-domain homolog that is present in Trifolium pretense (PNX92211.1) which, similar to our SNP-related ORF, contains additional TE-related domains downstream of the Znf-C2HC domain.…”
Section: Discussionsupporting
confidence: 88%
“…In the case of the SNP associated with seed length and width, dDocent_Contig_466_145, it is possible that the identified Znf-C2HC domain, downstream of the GAG domain of the TE is playing a role in gene transcription and thus affecting seed size. This would be similar to what has been reported for the ZnF-C2H2 domain encoding gene that was identified in M. truncatula and which was found to affect seed size [ 55 ]. Our further investigation of the protein sequence suggests that it is a truncated form of a similar multi-domain homolog that is present in Trifolium pretense (PNX92211.1) which, similar to our SNP-related ORF, contains additional TE-related domains downstream of the Znf-C2HC domain.…”
Section: Discussionsupporting
confidence: 88%
“…Four gene/protein families were found on chromosomic regions associated with ACR: Homeobox domain (WOX genes); Helix-turn-helix motif (LEAFY (LFY) protein); NAC domain (NAC TFs, MtNAM); and Zinc finger CCHC-type protein (Mt-Zn-CCHC gene). Previous reports have demonstrated the role of these families in either floral morphology, flowering initiation, differentiation of egg cells and zygotes, seed pod formation, translocation toward fruit under stress conditions, regulation of floral organ identity or seed size in Monotropa hypopitys [ 36 ], Arabidopsis thaliana [ 37 ], Citrullus lanatus [ 38 ] or Medicago truncatula [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger protein transcription factors play a vital role in plant growth and development, and biotic and abiotic stress responses [23]. Some previous studies showed that TaCCHC-ZF genes regulated plant growth and stress responses, such as AtRZ-1a, Mt-Zn-CCHC, and NTT [24][25][26][27]. Thus, the comprehensive bioinformatic analyses of TaCCHC-ZF gene family were performed to better understand the gene functions of TaCCHC-ZF genes due to the limited work on TaCCHC-ZF gene family.…”
Section: Discussionmentioning
confidence: 99%